Beginning HTML with CSS and XHTML - Schultz, David (Apress, 2012)
The World Wide Web has come a long way in a relatively short period of time. Since its debut in the early 1990s, the web has quickly evolved from an esoteric collection of academic papers into a fully fledged and pervasive medium, an equal to print, radio, and television. The web is a vast repository of information on every subject imaginable, from astrophysics and ancient philosophy to the care and feeding of hermit crabs. It has become an integral part of many people’s daily lives and is the platform for many aspects of modern business and commerce. But at its heart, the web is still just a way to share documents. This book will show you how to create documents of your own so you can share them on the web. You’ll become intimately familiar with the rules and constructs of HyperText Markup Language (HTML), the computer language the web is built on. It’s a simple language, and the basic rules are easy to pick up and put to use. HTML is a tool, and once you know how to use it, you’re limited only by your imagination.